THE ROLE OF FOLLOWER CHARACTERISTICS AS A MEDIATOR BETWEEN THE INFLUENCE OF INSPIRATIONAL LEADERSHIP AND HAPPINESS AT WORK - Pramono, Andi Eko Pramono (International Journal of Economics, Business, and Entrepreneurship, 2023)
Inspirational leadership is a leader who can invest time and develop intelligence in his work to inspire his followers. Inspirational leaders can encourage employee participation in achieving company goals. According to the 2019 Employee Happiness Index survey by Benify, it is stated that the banking industry is ranked 4th out of 5 industries in the category of employee engagement at work, and employee happiness in the banking industry is influenced by leaders who have good leadership and management characteristics. This study aims to analyze the role of follower characteristics as a mediator between the influence of inspirational leadership on happiness at work. The sample in this study amounted to 98 employees at PT. Bank Tabungan Negara (Persero), Tbk. Branch Office of Batam. The data collection method uses a questionnaire and the analysis method of this study uses Structural Equation Modeling (SEM) analysis through the Partial Least Square (PLS) approach using SmartPLS software version 3.3.3. The results of this study support the proposed hypothesis that there is a significant influence between inspirational leadership on happiness at work through follower characteristics mediation with path coefficient (0.423) and P-value (0.000 <0.05). The figure of a leader in inspirational leadership has a fundamental role that directly affects happiness at work.